Head-Movement-Emphasized Rehabilitation in Bilateral Vestibulopathy - Lehnen, Nadine; Kellerer, Silvy; Knorr, Alexander G.; Schlick, Cornelia; Jahn, Klaus; Schneider, Erich; Heuberger, Maria; Ramaioli, Cecilia (Frontiers in Neurology, 2018)
Objective: Although there is evidence that vestibular rehabilitation is useful for treating chronic bilateral vestibular hypofunction (BVH), the mechanisms for improvement, and the reasons why only some patients improve are still unclear. Clinical rehabilitation results and evidence from eye-head control in vestibular deficiency suggest that head movement is a crucial element of vestibular rehabilitation. In this study, we assess the effects of a specifically designed head-movement-based rehabilitation program on dynamic vision, and explore underlying mechanisms. Methods: Two adult patients (patients 1 and 2) with chronic BVH underwent two four-week interventions: 1) head-movement-emphasized rehabilitation (HME) with exercises based on active head movements, and 2) eye-movement-only rehabilitation (EMO), a control intervention with sham exercises without head movement. In a double-blind crossover design, the patients were randomized to first undergo EMO (patient 1) and - after a four-week washout - HME, and vice-versa (patient 2). Before each intervention and after a four-week follow-up patients’ dynamic vision, vestibulo-ocular reflex (VOR) gain, as well as re-fixation saccade behavior during passive head motion were assessed with the head impulse testing device – functional test (HITD-FT). Results: HME, not EMO, markedly improved perception with dynamic vision during passive head motion (HITD-FT score) increasing from 0% to 60% (patient 1) and 75% (patient 2). There was a combination of enhanced VOR, as well as improved saccadic compensation. Conclusion: Head movement seems to be an important element of rehabilitation for BVH. It improves dynamic vision with a combined VOR and compensatory saccade enhancement.